The struggles of sugar workers in Camagüey (1952-1955) (Islas, 2024)
Introduction: The main theme of the article is the struggles of sugar workers in Camagüey, and the object of study is the increase in workers' struggles against American companies and native landowners.Methods: Documentary analysis and interviews with labor leaders involved in these struggles between 1952 and 1955 were employed.Results: Many workers were detained for various reasons during these years, and hundreds of loads of sugarcane were burned in reaction to the workers' poor living conditions in the colonies and sugar mills.Conclusions: In the face of the general mobilization of sugar workers in the colonies and sugar mills, the strength and power of the workers against the exploiters were demonstrated.
Keywords: sugar workers' movement; strike; economy; landowning company; Camagüey